Effects of a Vigorous Gait on Mechanical Work and Oxygen Uptake during Treadmill Walking. Issue 1 (August 2014) - Azuma, Akihiro
This study was conducted to compare mechanical work during vigorous walking (which utilizes greater arm swings and step lengths) with that during normal walking and to examine whether individual differences (delta: vigorous walking – normal walking) in mechanical work during vigorous walking affected oxygen uptake (VO2 ). Six adult men ( M age = 28.5yr., SD = 3.9) performed normal and vigorous walking on a treadmill at 1.11, 1.53, and 1.94 m/sec. At all speeds, external work during vigorous walking was greater than that during normal walking, and the delta of total work was significantly correlated with that of VO2 . Thus, it was suggested that increased mechanical work (particularly total work) in vigorous walking would increase the metabolic cost.